The Impact of Return on Assets, Debt Equity Ratio, and Return on Equity on Stock Prices of Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange from 2019 to 2021 - Khomeiny Yunior; Amelia Putri; Tasya Dasfitri Rapmian Hutasoit; Juanda Arjuna Sirait (Kusuma Negara Business School, 2023)
The purpose of this study is to examine and analyze the influence of Return on Assets (ROA), Debt to Equity Ratio (DER), and Return on Equity (ROE) on stock prices in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange. In conducting the analysis, there are various types of ratios with different functions that can be used. Of the numerous ratios, the financial ratios used in this study are ROA, DER, and ROE as independent variables, and the Stock Price as the dependent variable. The sample collection technique in this study used a purposive sampling technique with 30 companies selected as samples from a population of 54 food and beverage sector industries for the 2019-2021 period, which are listed on the Indonesia Stock Exchange (IDX). The method in this study uses a quantitative approach and the data source in this study uses secondary data sources that include documentation studies. This method is used to gather data from companies related to the variables under study. In testing the hypothesis, this study uses Multiple Linear Regression Analysis. From the hypothesis testing in the study, it was found that, simultaneously, ROA, DER, and ROE, which are the independent variables, influence the Stock Price of food and beverage manufacturing companies listed on IDX for the 2019-2021 period, which is the dependent variable. In addition, the results of partial hypothesis testing in this study found that, partially, ROA, DER, and ROE do not affect the Stock Price of manufacturing companies listed on the IDX for the 2019-2021 period.